Assessment of the patient with syncope. Issue 7 (July 2022) - Gill, Harjeevan
Syncope is a transient loss of consciousness due to cerebral hypoperfusion, characterised by rapid onset, short duration and spontaneous complete recovery. The causes range from self-limiting episodes of reflex syncope to conditions that can precede severe illness or death. GPs often provide the first assessment of patients with syncope and this article aims to guide the assessment of these patients to help identify the cause. This will include exploring the common causes of syncope, history taking, examination, investigations, red flags in syncope and management.